The Government and Market Performance in the Process of Iran's Economic Growth - Mohammad Raza Monjazeb; Hossein Mohamadi; Abbas Hosseini Sohi (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2006)
In this article with an introduction to market economy versus planned economy, we review different economic doctrines by looking at their roles and efficiency of each one of them to show that the  selection  and  allocation  of  resources is according  to  economic  efficiency, culture, scarcity to reachness  of resources and etc. Then we review the public companies performance and privatization in Iran, and according to data for Iran (1959-2002), we estimate the production- investment elasticity by a growth model and compare  them  with  together. The result of this article shows that there is found a positive  effect  of  private  and  governmental  investment  on production  growth  by statistical  methods  and  tests. Also there is no difference between these two variables. So without structural reforms, we can not change the growth trend in Iran.